PERSEPSI GENERASI Z TERHADAP PERNIKAHAN DINI: STUDI ANALITIS DALAM KERANGKA MAQASHID SYARIAH - Maimun; Fikri, Arif; Zaharah, Rita (LPPM STAI DARUSSALAM LAMPUNG, 2025)
Abstract: This research explores Generation Z’s perspectives on early marriage through the lens of Maqashid Syariah. The study reveals that most members of Generation Z oppose early marriage, considering it an obstacle to personal growth, education, and economic stability. However, some still view it as a viable option under certain conditions, particularly in relation to economic and cultural influences. From a Maqashid Syariah standpoint, early marriage has diverse implications. Concerning hifz ad-din , it should be approached with adequate mental and spiritual preparedness to avoid potential harm. In terms of hifz an-nafs , the physical and psychological health risks, especially for women, are significant considerations. Regarding hifz al-aql, interrupted education due to early marriage can negatively impact an individual's future prospects. From the hifz an-nasl perspective, insufficient readiness to raise children may affect the well-being of future generations. Lastly, in the aspect of hifz al-mal, financial instability among young couples often results in economic hardship. This study offers crucial insights for policymakers and scholars in developing preventive measures against early marriage in alignment with Maqāṣid Syariah principles. It emphasizes the need to consider not only religious teachings but also the broader socio-economic consequences in decision-making. Keywords: Generation Z, Early Marriage, Maqāṣid Syariah, Perception, Islamic Law